Keputusan Penggunaan Layanan Go-Jek di DKI Jakarta Berdasarkan Pengaruh Service Marketing Mix - Andykha Pratama Anau; Wasi Bagasworo (STIE Indonesia Banking School, 2016)
Community these days believe in efficiency and simplicity to access a mobile application, especially for purchasing a certain product. This indicates a wider opportunity for companies to extend their consumers by using the internet. Go-Jek, as a pioneer of mobile application, links ‘ojek’ drivers to deliver a one-stop-shop convenience service for Indonesian citizen. It answers these huge opportunities by expanding its services including transportation, instant courier, GO-FOOD and shopping using two wheels driver. The main purposeof this research is to measure the influence of service marketing mix through purchasing decision in DKI Jakarta - study on Go-Jek user. Data were collected by the writer based on Go-Jek customers’ respondents especially in DKI Jakarta. Quantitative analysis was applied to understand and to measure the hypothesis intention in this research. The result indicates the significant influences between the product, prices, places, promotions, people, process, and physical evidence on purchasing decision. Hence, physical evidence is the most significant variable for a customer in DKI Jakarta toward its purchasing decision. Go-Jek motorbike supported by its proper condition, its completeness riding tools, its cleanliness, its conveniences during riding. They provided a well-kept helmet and several types of equipment for the customers. In addition, Go-Jek drivers maintain their own tidiest and appearances. These are the variable indicators which influence the customer decision for using GoJek services. The results suggested Go-Jek maintaining their supervision and controlling the standard operation for delivering its services to its customers, and punctuality toward responding to the order of the customers